Syntheses, crystal structures and luminescent properties of two new Zn(II) coordination polymers based on a dicarboxylate and different imidazole-containing ligands. Issue 10 (18th May 2016) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract: To investigate the effect of different imidazole-containing ligands on the structure of coordination polymers, two new Zn(II) coordination polymers based on 1, 4-cyclohexanedicarboxylic acid (H2 cda) and two different imidazole-containing ligands, [Zn(cda)(bib)0.5 ]n (1 ) and [Zn(cda)(bmib)0.5 ]n (2 ) (bib = 1, 4-bis(imidazol-1-yl)benzene and bmib = 1, 4-bis(2-methylimidazol-3-ium-yl)benzene), have been synthesized and characterized by single-crystal X-ray diffraction. Complex1 shows a 3-D structure with point symbol (4.8 2 .10 3 ).(4.8 2 ). Complex2 displays a 2-D layer structure with an –AB– stacking sequence. Abstract :